The regulation and function of CD20: an “enigma” of B-cell biology and targeted therapy - Pavlasova, Gabriela; Mraz, Marek (Haematologica (Roma), 2020)
The introduction of anti-CD20 monoclonal antibodies such as rituximab, ofatumumab, or obinutuzumab improved the therapy of B-cell malignancies even though the precise physiological role and regulation of CD20 remains unclear. Furthermore, CD20 expression is highly variable between different B-cell malignancies, patients with the same malignancy, and even between intraclonal subpopulations in an individual patient. Several epigenetic (EZH2, HDAC1/2, HDAC1/4, HDAC6, complex Sin3A-HDAC1) and transcription factors (USF, OCT1/2, PU.1, PiP, ELK1, ETS1, SP1, NFκB, FOXO1, CREM, SMAD2/3) regulating CD20 expression (encoded by ) have been characterized. CD20 is induced in the context of microenvironmental interactions by CXCR4/SDF1 (CXCL12) chemokine signaling and the molecular function of CD20 has been linked to the signaling propensity of B-cell receptor (BCR). CD20 has also been shown to interact with multiple other surface proteins on B cells (such as CD40, MHCII, CD53, CD81, CD82, and CBP). Current efforts to combine anti-CD20 monoclonal antibodies with BCR signaling inhibitors targeting BTK or PI3K (ibrutinib, acalabrutinib, idelalisib, duvelisib) or BH3-mimetics (venetoclax) lead to the necessity to better understand both the mechanisms of regulation and the biological functions of CD20. This is underscored by the observation that CD20 is decreased in response to the "BCR inhibitor" ibrutinib which largely prevents its successful combination with rituximab. Several small molecules (such as histone deacetylase inhibitors, DNA methyl-transferase inhibitors, aurora kinase A/B inhibitors, farnesyltransferase inhibitors, FOXO1 inhibitors, and bryostatin-1) are being tested to upregulate cell-surface CD20 levels and increase the efficacy of anti-CD20 monoclonal antibodies. Herein, we review the current understanding of CD20 function, and the mechanisms of its regulation in normal and malignant B cells, highlighting the therapeutic implications.